Study of association between hypovitminosis D and fibroid uterus - Choudhary, Sangeeta; Shukla, Mala; Joshi, Ruchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Fibroid uterus or leiomyoma is a benign tumour composed mainly of unicellular smooth muscle cells with varying amounts of fibrous connective tissue. UF are associated with significant morbidity as it presents in form of abnormal uterine bleeding, anaemia, pelvic pain, subfertility, and obstetric complications and causes financial burden on the patient. Recent studies have shown the critical role that vitamin D plays in fibroid formation, with individual fibroids expressing lower levels of vitamin D receptors than adjacent healthy tissue, making vitamin D deficiency a crucial, yet preventable risk factor. Methods: This was cross-sectional observational study. It was conducted on 140 female patients aged (18 to 50 years) presenting to the OPD of department of obstetrics and gynecology at NDMC & Hindu Rao Hospital during July 2019 to June 2020. 70 women had uterine fibroids on ultrasound and treated as cases and rest healthy women without fibroids served as controls. All women were subjected to ultrasound examination of uterus followed by serum vitamin D3 levels. Results: The mean value of vitamin D levels in cases was 12.81±8.56 ng/ml and in controls it was 19.83±9.21 ng/ml with p value<0.0001. Thus, it was statistically significant lower in cases of fibroid uterus as compared to controls. Secondary incidental outcomes were found between vitamin D3 level and BMI as fibroids occur statistically significantly more often in patient having of BMI ≥25 kg/m2. Also, menorrhagia and dysmenorrhea were the major complaints in 62.5% of cases followed by lowers abdominal pain and dyspareunia. Conclusions: Our study reached significance in the inverse correlation between fibroids and vitamin D levels at the primary outcome level. Larger prospective longitudinal studies drawing on more number and eliminating confounding variables are needed.